MAKING TEMPERATURE ALARM ON IRON-BASED BLYNK PLAYSTORE APPLICATION - Sembodo, Budi Prijo; Mahardhika, Bagus Prima (Tibuana, 2020)
In this era, practical, effectiveness andsafety in activities are the necessities anddemands of life where almost all people makeit a priority in their lives. Effectiveness inactivities will be obtained by the availability oftechnology that supports it all. Various effortshave been made by humans to make neatclothes so as to create a clean impression andsupport various activities, an example of theresults of human efforts that are widely used toovercome this is by using an iron. In addition,the majority of the equipment still requiresmanual operation. Apart from the practicalside, but does not eliminate the safety side. Sohere the author is interested in conductingresearch on the practicality of use which islater expected to make the use of irons moreefficient, practical and safe. The measuredparameter is how the DS18B20 temperaturesensor functions as a temperature responsereceiver that sends a signal to the temperaturesensor module which will activate ordeactivate the iron through a smartphone. Theresults of this study that the device is able tosend a signal to the smartphone and if thetemperature produced by the iron exceeds themaximum limit a warning sign will appear onthe smartphone, and the user can operate theiron online and remotely using a smartphone.The speed of response received by the tool isalso to be forwarded to the iron or smartphoneis also in accordance with needs